Teaching Performance of Lecturers during Pandemic Based on Knowledge and Expertise in Salatiga - Hardi Utomo; Meida Rachmawati (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The Covid-19 pandemic has forced teaching and learning activities to be carried out from the homes of students online (on-line) from basic education to tertiary institutions. In a pandemic where learning activities are carried out without face-to-face, namely fully online, lecturers must also have an obligation to adapt. For this reason, the teaching performance of lecturers during the pandemic needs to be seen in order to see how well the lecturers' performance in the field of teaching during the pandemic is. With this pandemic period, it will also be a knowledge gap to see the readiness of lecturers in adapting to the changes that occur. Based on this, this study will look at how the performance of lecturers in the field of teaching in the city of Salatiga during the pandemic. The sources of data in this study are lecturers in the city of Salatiga. The research was carried out using descriptive analysis method while data collection was carried out using a survey method by distributing questionnaires. This questionnaire uses a Likert scale to measure the perceptions of the lecturers. Based on the research that has been done, the teaching performance of lecturers during the pandemic is at a good level or ready for teaching planning and evaluation. This means that in the opinion of the respondents they have performed well in these two areas so that they are ready to plan and evaluate online teaching during the pandemic.